2012
DOI: 10.1016/j.brainresbull.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The opposite effect of a 5-HT1B receptor agonist on 5-HT synthesis, as well as its resistant counterpart, in an animal model of depression

Abstract: Flinders Sensitive Line (FSL) rat is as an animal model of depression with altered parameters of the serotonergic (5-HT) system function (5-HT synthesis rates, tissue concentrations, release, receptor density and affinity), as well as an altered sensitivity of these parameters to different 5-HT based antidepressants. The effects of acute and chronic treatments with the 5-HT 1B agonist, CP-94253 on 5-HT synthesis, in the FSL rats and the Flinders Resistant Line (FRL) controls were measured using α-[ 14 C]methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…The results of the present study including the fact that the pharmacological validity of the FST and TST was reproduced by the U-field test ( Fig. 3 ) support the envision that the TST and FST measure psychomotor retardation, which were previously proposed [ 21 , 22 , 23 ] and is a core symptom of depression suggested by the Diagnostic and Statistical Manual of Mental Disorders (DSM-V).…”
Section: Discussionsupporting
confidence: 88%
“…The results of the present study including the fact that the pharmacological validity of the FST and TST was reproduced by the U-field test ( Fig. 3 ) support the envision that the TST and FST measure psychomotor retardation, which were previously proposed [ 21 , 22 , 23 ] and is a core symptom of depression suggested by the Diagnostic and Statistical Manual of Mental Disorders (DSM-V).…”
Section: Discussionsupporting
confidence: 88%
“… 89 , 90 It has been shown that the 5-HT 1B receptor agonist CP-94253 can modulate 5-HT synthesis in the Flinders Sensitive Line rat, an animal model of depression. 91 In intracerebral microdialysis studies, stimulation of 5-HT 1B receptors by RU 24969 potentiated the antidepressant-like effects of SSRIs and imipramine. 92 Additionally, 5-HT 1B receptor stimulation with the selective agonist CP-94253 in mice displayed an antidepressant-like profile in the forced swim test.…”
Section: Modulation Of Glutamate Transmission By 5-ht Receptorsmentioning
confidence: 99%
“…The 5-HT 1B receptor has been implicated in the pathophysiology and treatment of depression 89 90 It has been shown that the 5-HT 1B receptor agonist CP-94253 can modulate 5-HT synthesis in the Flinders Sensitive Line rat, an animal model of depression 91 . In intracerebral microdialysis studies, stimulation of 5-HT 1B receptors by RU 24969 potentiated the antidepressant-like effects of SSRIs and imipramine 92 .…”
Section: Modulation Of Glutamate Transmission By 5-ht Receptorsmentioning
confidence: 99%
“…Such data would depend on the duration of 5-HT1B modulations and presence of antidepressant-like effect [159].…”
Section: -Ht1b and Depressionmentioning
confidence: 99%